2015
DOI: 10.1055/s-0034-1398628
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Treatment can Overcome Glucocorticoid Resistance in Childhood B-cell Precursor Acute Lymphoblastic Leukemia Cell Lines

Abstract: The proteasome inhibitor bortezomib seems to sensitize gc-resistant childhood ALL cells for prednisolone-induced cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Furthermore, higher levels of VCP/p97 were identified in poor vs. good prednisone responders by analyzing leukemic blasts in patients with childhood acute lymphoblastic leukemia (ALL) [106]. Similarly, another study confirmed a role for VCP/p97 in glucocorticoidresistant leukemic cells [120]. Notably, a proteomic approach indicated that VCP/p97 was the most abundant protein involved in exosome generation and secretion in T-cell leukemia Jurkat cells; indeed, VCP/p97 inhibition prevented tumor exosome secretion, thus highlighting a potential novel mechanism of VCP/p97 in tumorigenesis [107].…”
Section: Vcp/p97 In Hematological Cancersmentioning
confidence: 87%
“…Furthermore, higher levels of VCP/p97 were identified in poor vs. good prednisone responders by analyzing leukemic blasts in patients with childhood acute lymphoblastic leukemia (ALL) [106]. Similarly, another study confirmed a role for VCP/p97 in glucocorticoidresistant leukemic cells [120]. Notably, a proteomic approach indicated that VCP/p97 was the most abundant protein involved in exosome generation and secretion in T-cell leukemia Jurkat cells; indeed, VCP/p97 inhibition prevented tumor exosome secretion, thus highlighting a potential novel mechanism of VCP/p97 in tumorigenesis [107].…”
Section: Vcp/p97 In Hematological Cancersmentioning
confidence: 87%
“…In recent years, the effectiveness of Bortezomib was also tested for the treatment of acute lymphoblastic leukemia. It was shown that bortezomib can sensitize in-vitro GC-resistant childhood B-cell precursor leukemia cell lines, MHH-cALL-2 and MHH-cALL-3, to prednisolone-induced cell death via inhibiting the proteasome (Junk et al 2015). The use of proteasome inhibitors to sensitize GC-resistant ALL cells was supported by detecting that high expression of valosin-containing protein (VCP), a member of the ubiquitin proteasome degradation system (UPS), is associated with poor response to prednisolone treatment in childhood ALL patients (Lauten et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib (BTZ) is a small molecule proteasome inhibitor that mainly inhibits 26S proteasome, thereby inhibiting many processes involved in cell cycle regulation, apoptosis, cell adhesion, angiogenesis, and chemical resistance [165]. Studies have shown that BTZ can increase the sensitivity of cancer cells to chemotherapeutic drugs and effectively reduce the resistance of cancer cells to chemotherapy [166]. BTZ has a significant cytotoxic effect on NSCLC.…”
Section: Advances In the Combination Of Cell Cycle Regulation And Che...mentioning
confidence: 99%